PECULIARITIES OF PATIENTS' PERCEPTION AND UNDERSTANDING OF INSTRUCTIONS FOR MEDICAL APPLICATION OF DRUGS - L. M. Unhurian (Фармация и фармакология (Пятигорск))
The article presents the results of an opinion poll of pharmacies visitors in Odessa, Ukraine about understanding and interpretation of the instructions for medical use of drugs. Results of the study identified a particular patients’ perception of the semantic content of the instructions texts and the need for further information and methodological work to improve their communicative accuracy.